During the Audit Process, The Main Means of Composition, Structure and Methods of Technical Condition Analysis - A. Mamajonov; R. Khabibullaeva (Research Parks Publishers, 2023)
In this article, the authors discussed the methods of analyzing the composition, structure and technical condition of the main tools during the audit process.